Phenotype of V2-derived interneurons and their relationship to the axon guidance molecule EphA4 in the developing mouse spinal cord. - Lundfald, L; Restrepo, C; Butt, S; Peng, C; Droho, S; Endo, T; Zeilhofer, H; Sharma, K; Kiehn, O (2007)
The ventral spinal cord consists of interneuron groups arising from distinct, genetically defined, progenitor domains along the dorsoventral axis. Many of these interneuron groups settle in the ventral spinal cord which, in mammals, contains the central pattern generator for locomotion. In order to better understand the locomotor networks, we have used different transgenic mice for anatomical characterization of one of these interneuron groups, called V2 interneurons. Neurons in this group are either V2a interneurons marked by the postmitotic expression of the transcription factor Chx10, or V2b interneurons which express the transcription factors Gata2 and Gata3. We found that all V2a and most V2b interneurons were ipsilaterally projecting in embryos as well as in newborns. V2a interneurons were for the most part glutamatergic while V2b interneurons were mainly GABAergic or glycinergic. Furthermore, we demonstrated that a large proportion of V2 interneurons expressed the axon guidance molecule EphA4, a molecule previously shown to be important for correct organization of locomotor networks. We also showed that V2 interneurons and motor neurons alone did not account for all EphA4-expressing neurons in the spinal cord. Together, these findings enable a better interpretation of neural networks underlying locomotion, and open up the search for as yet unknown components of the mammalian central pattern generator.